Pengaruh Sistem Pengukuran Kinerja Dan Sistem Pengendalian Manajemen Terhadap Kinerja Badan Pendapatan Daerah Provinsi Sulawesi Utara Dimasa Pandemi Covid-19 - Marlita Wilke Maria Lombogia (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Performance designed and defined to reach and encourage the organization to achieve its strategic objectives. This study aims to determine the effect on the performance measurement system and performance control system of the Regional Revenue Agency of North Sulawesi Province during the Covid 19 pandemic. This type of research is causal associative. The population of this study was from 292 State Civil Apparatus who worked in the Regional Revenue Agency of North Sulawesi Province as many as 61 respondents and the sample was taken using purposive sampling method so that the total sample was 50 respondents. The data source of this research is primary data obtained through distributing questionnaires to the Head of the UPTD/Head of Subdivision. The data analysis technique used data quality test, descriptive statistical analysis, classical assumption test and hypothesis testing. The results showed that partially the performance measurement system variables and control variables had a positive and significant effect on the performance of the Regional Revenue Agency of North Sulawesi Province.Â